Big Game, Small World : A Basketball Adventure - Wolff, Alexander, 1957- (Book collections on Project MUSE., 2022)
"During the late 1990s, eminent basketball journalist Alexander Wolff traveled the globe to determine how a game invented by a Canadian clergyman became an international phenomenon. Big Game, Small World presents Wolff's dispatches from sixteen countries spread across five continents and multiple US states, in which he asks: What can the game tell us about the world? And what can the world tell us about the game? Whether traveling to Bhutan to challenge the King to a pickup game, exploring the women's game in Brazil, or covering the Afrobasket tournament in Luanda, Angola, during a civil war, Wolff shows how basketball has the power to define an individual, a culture, and even a country.This updated twentieth anniversary edition features a new preface in which Wolff outlines the contemporary rise of athlete-activists while discussing the increasing NBA dominance of marquee international players like Luka DoncÌ⁺icÌ and Giannis Antetokounmpo. A loving celebration of basketball, Big Game, Small World is one of the most insightful books ever written about the game."--